2002
DOI: 10.1080/147641702321136246
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy of freckles and lentigines with quasi-continuous, frequency-doubled, Nd:YAG (532 nm) laser in Fitzpatrick skin type IV: a 24-month follow-up

Abstract: The quasi-continuous, frequency-doubled Nd:Y AG (532 nm) laser safely and effectively treats freckles and lentigines in Fitzpatrick skin type IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…It has been suggested that the photomechanical effect of QS lasers may not be desirable when used in the removal of lentigines in pigmented skin type [6,7,10]. Other studies have recently confirmed the effectiveness of long-pulsed 532 nm laser in the treatment of lentigines in dark skin patients [11]. The IPL, which emits a broadband of visible light from a non-coherent filtered flashlamp, produces only photothermal effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the photomechanical effect of QS lasers may not be desirable when used in the removal of lentigines in pigmented skin type [6,7,10]. Other studies have recently confirmed the effectiveness of long-pulsed 532 nm laser in the treatment of lentigines in dark skin patients [11]. The IPL, which emits a broadband of visible light from a non-coherent filtered flashlamp, produces only photothermal effects.…”
Section: Discussionmentioning
confidence: 99%
“…11 The pulse duration applied was 1.6 microseconds; exposure time was 0.01 second to continuous; and spot size 2 mm. Irradiation was delivered during 3 to 8 sessions at 4-to 12-week intervals.…”
Section: Laser Therapymentioning
confidence: 99%
“…24 Side effects included hypo-pigmentation (25%), textural changes (15%), and hyperpigmentation (10%), but these were mild and resolved within six months. Rosenbach et al treated 21 patients with solar lentigines two times with an alexandrite laser (7 mm spot, fluence 35-40 J/cm 2 , 5 ms pulse duration) and noted excellent improvement in 19 patients.…”
Section: Casementioning
confidence: 99%
“…3-5, to produce lesion clearance compared to Q-switched lasers. 13,24 Café-au-lait macules Café-au-lait macules (CALMs) are well-circumscribed brown macules and patches that may occur as isolated lesions or associated with neurocutaneous syndromes like neurofibromatosis or McCune-Albright syndrome. They appear at birth and may increase in number with age and are persistent.…”
Section: Casementioning
confidence: 99%